Scanning and transmission electron microscopy of the cells forming the hepatic sinusoidal wall of rat in acetaminophen- and Escherichia coli endotoxin-induced hepatotoxicity. Issue 1 (March 2017) - Nafady, Allam Mohamed; Ahmed, Omar Bauomy; Ghafeer, Hemmat Haridy
Abstract: Drugs and xenobiotics as well as bacterial endotoxins may reach the liver either systematically or after intestinal absorption. Therefore, cells lining the sinusoidal wall form the last barrier before blood constituents get in contact with the parenchymal cells. In this work, the ultrastructure of the cells forming the sinusoidal wall was studied after acetaminophen and Escherichia coli endotoxin treatments. Rats received acetaminophen at a dose of 1000 mg/kg body weight by intraperitoneal injection once in acute and four times with a 1-week interval in chronic treatments, and E. coli endotoxin at a dose of 5 mg/kg of body weight by intraperitoneal injection once in acute and four times with a 1-week interval in chronic treatments. Tissue samples were collected for scanning and transmission electron microscopy. Swelling of sinusoidal endothelial cells was noticed in both acute intoxicated groups with narrowing of the fenestrae, whereas large gaps were formed in chronic toxicity. Activation of Kupffer cells was a prominent common feature between the four toxicity groups. Interestingly, hepatic stellate cell activation was evident in both chronic acetaminophen and chronic endotoxin groups. Large amounts of collagen fibers were seen surrounding the hepatic stellate cells and in Disse space.